Nuclear Magnetic Resonance Studies of Coordination Compounds - L.M. Venanzi (CHIMIA)
The applicability of donor and metal atom nmr to coordination chemistry is briefly reviewed. The following structural studies are discussed: (1) the use of 31P resonances for the determination of molecular geometry of complexes [RuCl2(QP)], [Fe(NCS)2(QP)] and [W(CO)3(QP)] (QP = [o-Ph2P•C6H4]3P); (2) the use of 13C resonances for the formulation of the carbon moiety C8H11•OCH3 coordinated to a palladium atom and (3) the use of 14N to establish the nature of the donor atom in a number of thiocyanato-complexes. It is further shown that proton-noise decoupled 31P spectra can be conveniently used to obtain activation parameters for ligand exchange in complexes [Ni{P(OR)3}4]. A possible interpretation of changes in 1|J105Pt-15N| parameters, in platinum complexes containing primary amines, in terms of selective hybridization at the platinum atom is presented. Finally, possible future developments in nmr studies of coordination compounds are briefly outlined.